Influence Factors on EGS Geothermal Reservoir Extraction Performance - Haitao Wang; Lijuan Wang; Zude Cheng (Geofluids)
The heat extraction performance of the enhanced geothermal system is simulated by using COMSOL software. The effects of six factors, such as the thermal conductivity of heat reservoir, matrix permeability, fracture width, injection temperature, injection flow rate, and the number of wells, on the heat extraction performance of EGS heat reservoir for 40 years are analyzed. The results show that the matrix permeability and injection flow are the main factors affecting the heat production performance of the EGS geothermal reservoir, while the thermal conductivity, fracture width, and injection temperature have little effect on the heat production performance of the EGS geothermal reservoir. Although increasing the number of production wells can improve the uneven distribution of the flow field to improve the system heat performance, taking into account the existing drilling technology and cost, the cost is higher, and the two-well system is still the basic form of absorbing rock heat.